SERIES: ECONOMICS APPLIED TO PROCESS ENGINEERING (PART 9) MANAGEMENT AND PERFORMANCE MEASUREMENT ANALYSIS GROSS PROFIT - Porlles L., José (2008)
Along the lines of strengthening the competitive advantages of engineers processes, in this ninth edition suggested the use of technical analysis of gross profit to explain the variations in sales and The cost of sales that affect the results of management. With the methodologies that will illustrate both the management and directors of the centers of responsibility (CR) will have indicators to be fit in explaining the causes, mainly from unfavorable changes. In this way will be better able to argue the improvement plans arising out to implement changes that are necessary.